2009
DOI: 10.1523/jneurosci.2759-09.2009
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous with Your Feelings: Sensorimotor γ Band and Empathy for Pain

Abstract: Neuroscience studies on the social sharing of observed or imagined pain focused on whether empathic pain resonance is linked to affective or sensory nodes of the pain matrix. However, empathy, like other complex cognitive processes, is inherently linked to the activation of functional networks rather than of separate brain areas. Here, we used magnetoencephalography (MEG) to explore the relationship between empathy and functional coupling of neuronal activity in primary somatosensory (SI) and motor (MI) cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 69 publications
3
36
0
Order By: Relevance
“…A recent study demonstrated that TMS over SI selectively reduced the typical corticospinal mapping of biomechanically impossible movements [Fadiga et al, 1995[Fadiga et al, , 2005Romani et al, 2005], which were associated with aversive somatic feelings, without impacting mirror responses to possible movements that did not evoke somatic feelings in the observer. Modulation of SI activity that is contingent upon observation of others' pain has also been described [Betti et al, 2009;Bufalari et al, 2007]. Therefore, it seems that the mirror function of SI is that of preferentially encoding the somatic component of action simulation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…A recent study demonstrated that TMS over SI selectively reduced the typical corticospinal mapping of biomechanically impossible movements [Fadiga et al, 1995[Fadiga et al, , 2005Romani et al, 2005], which were associated with aversive somatic feelings, without impacting mirror responses to possible movements that did not evoke somatic feelings in the observer. Modulation of SI activity that is contingent upon observation of others' pain has also been described [Betti et al, 2009;Bufalari et al, 2007]. Therefore, it seems that the mirror function of SI is that of preferentially encoding the somatic component of action simulation.…”
Section: Discussionmentioning
confidence: 95%
“…Action observation and execution increases neural activity in both motor and somatosensory areas [Rizzolatti and Craighero, 2004]. Crucially, making the perceived action painful or more salient from a tactile or proprioceptive point of view causes an increase of the activity in SI Betti et al, 2009;Bufalari et al, 2007;Costantini et al, 2005]. A recent study demonstrated that TMS over SI selectively reduced the typical corticospinal mapping of biomechanically impossible movements [Fadiga et al, 1995[Fadiga et al, , 2005Romani et al, 2005], which were associated with aversive somatic feelings, without impacting mirror responses to possible movements that did not evoke somatic feelings in the observer.…”
Section: Discussionmentioning
confidence: 99%
“…This role is not limited to neural synchrony of local brain networks, but also extends to large-scale interactions. [40][41][42][43] Therefore, investigations of connectivity, rather than power, in the resting state might contribute to disentangling the discrepancies of previous research, providing new insights into the role of gamma-band connectivity in the pathophysiology of the disorder. So far, only 2 studies have assessed gamma-band synchronization in patients with schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this mechanism may also be important for multisensory interactions contributing to pain perception. First evidence supporting this assumption derives from the study by Betti et al [2], who reported enhanced functional coupling between primary sensory and motor cortex through neural coherence in the gamma band when participants are presented with needle-penetrating-hand clips. Thus, we suggest that the examination of oscillatory activity is a promising research target for future studies on pain processing in multisensory environments.…”
Section: Discussionmentioning
confidence: 98%
“…A more recent MEG study further investigated the effect of observing painful events on neuronal processing within the pain matrix [2]. The authors addressed the interplay of somatosensory and motor areas during the presentation of needlepenetrating-hand clips.…”
Section: Box 2: Human Experimental Pain Modelsmentioning
confidence: 99%